PROMOSI PADA OBJEK WISATA QUEEN STAR WATERPARK DI SIAK - Handi, Mhd Hamzah; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research aims to describe the implementation of the promotion and identify the obstacles faced by Queen Star Waterpark as the only largest water recreation attraction in Siak Regency, Riau. Queen Star Waterpark has great potential as a superior tourist destination because it offers modern facilities, strategic location, and family attraction. However, in an effort to attract more visitors, promotion becomes a very important element. The research method used is qualitative with a descriptive approach. Data is obtained through observation, interviews with eight informants (managers, employees, local communities, and visitors), as well as documentation. Research results show that the promotion of Queen Star Waterpark is carried out through print media (brochure), electronic media (Instagram and Facebook), as well as public relations strategies through bundling packages. This effort is considered quite effective in reaching the local community, but still has limitations in reaching a wider audience. The main obstacles found include the limited use of modern digital media, lack of variety of promotional content, and competition with other tourist destinations in the surrounding area. The research suggests that the management should expand the use of video-based social media such as TikTok, increase the creativity of digital content, and establish collaboration with the local tourist community. With a more innovative and adaptive promotion strategy, Queen Star Waterpark has the potential to become a family tourism icon as well as increase its contribution to the Siak Regency tourism sector. Keywords:Promotion,Tour,Queen Star Water Park,Social Media,Visitors